Vision, Quality of Life and Depressive Symptoms After First Eye Cataract Surgery - Fraser, Michelle; Meuleners, Helen; Lee, Andy; Ng, Jonathon; Morlet, Nigel (Wiley-Blackwell Publishing Asia, 2013)
Background: Cataract affects not only vision, but also performance of everyday tasks, participation in social activities, quality of life and possibly depression. Depression is a major health issue for older adults. It is estimated that 6%–20% of community-dwelling older Australians experience depression. The aim of this study was to investigate changes in vision related quality of life and depressive symptoms after first eye cataract surgery and to determine which visual measures affect the change in these outcomes. Methods: In 2009 and 2010, 99 participants with bilateral cataract were recruited. Visual measures including visual acuity, contrast sensitivity and stereopsis were assessed 1 week before and 12 weeks after first eye cataract surgery. Vision-related quality of life was measured using the 25-item National Eye Institute Visual Function Questionnaire. Depressive symptoms were assessed by the 20-item Center for Epidemiological Studies Depression Scale. Separate regression analyses were undertaken to determine the association between visual measures and changes in vision-related quality of life and depressive symptoms after first eye cataract surgery. Results: Overall, vision-related quality of life improved after first eye cataract surgery. There was a small, non-clinically significant improvement in depressive symptoms after surgery. Improvement in vision-related quality of life after first eye cataract surgery was associated with improved contrast sensitivity in the operated eye (P < 0.001), whereas improvement in depressive symptoms after surgery was associated with improved stereopsis (P = 0.032).Conclusions: Contrast sensitivity and stereopsis, but not visual acuity, were significant factors affecting improvement in vision-related quality of life or depressive symptoms after first eye cataract surgery.